Penerapan Metode TOPSIS Sebagai Pendukung Keputusan Pemilihan Layanan Akomodasi di Destinasi Wisata Pulau - Yerik Afrianto Singgalen (Universitas Budi Darma, 2023)
The selection of accommodation services in a tourist destination can be adjusted to the preferences of tourists. This study aims to recommend the TOPSIS method as a decision support system in the selection of accommodation services in tourist destinations, based on case studies of Morotai Island tourist destinations. The application of the TOPSIS method as decision support for the selection of accommodation services in Morotai Island tourist destinations consists of four stages as follows: the stage of making a normalized matrix, weighted normalized matrix manufacturing stage; steps determine the matrix of positive and negative ideal solutions; The step determines the preference value for each alternative. The criteria set are as follows: room price as a cost with an importance weight of 5; distance of the hotel to the destination as a benefit with an importance weight of 3; room type/class as a benefit with an importance weight of 4; hotel amenities as a benefit with an importance weight of 4; Service rating as a benefit with importance weight 4. Specifically, the accommodation service providers focused on are Daloha Resort; Metita Beach and Dive Resort; Moro Ma Doto; Molokai by Sahid Hotel; and Ria Hotel. The results of this study showed that the alternative with the highest preference value was Metita Beach and Dive Resort, with a value of 0.764348724, then Molokai by Sahid Hotel, with a value of 0.626002478. In addition, Daloha Resort has a value of 0.616994938, and Ria Hotel has a value of 0.61630669. Also, Moro Ma Doto has a value of 0.363441753. This suggests that travelers prioritizing price as the dominant factor with weight critical (5) will choose Metita Beach and Dive Resort. If the importance weight of each criterion is changed according to the traveler's perspective, the system will recommend different accommodation services. Thus, tourists can use the TOPSIS method in choosing accommodation services and give importance weight according to individual preferences. Therefore, the TOPSIS method can be used in selecting accommodation services in various tourist destinations.